THE USE OF ULAP – ULAP IN SACRED BUILDINGS IN DENPASAR CITY - Nyoman Kiriana; I Gusti Ketut Dalem; Ni Nyoman Sri Widiasih (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2023)
This paper aimed to describe and explore the role of ulap-ulap buildings as sacred buildings in Denpasar City. It often happens when installing ulap-ulap because of the role of ulap-ulap buildings as sacred buildings in Denpasar City. It often happens when installing ulap-ulap that has been made by the Sulinggih or the authorities in reverse. The ulap-ulap that should have been installed on the palinggih Kamulan is then installed on the palinggih Taksu. As well as the wrong placement of aksaradasaksara rotation, where the direction of purwa should be placed above but is placed on the right side. Namely, the existence of ulap-ulap in the sacred building in Denpasar City is an upakara to make ulap-ulap. The forms of upakara used in making ulap-ulap are of several levels and consist of Nista, Madya, and Utama. Second, the types of ulap-ulap in the sacred building consist of padma, meru, gedong, bale, tugu, kori, and parhyangan. Third, the implications of ulap-ulap for Hindus in Denpasar City have implications for strengthening belief in God, developing Balinese culture, preserving Balinese Script in Hinduism, developing aesthetic creativity, and as the basis for practicing Tri Hita Karana.